Impacts of COVID-19 on the mental health of professors at a Cuban medical university - Herrera Masó, Juan Rubén; Lardoeyt Ferrer, Roberto (Spanish Journal of Medical Education, 2023)
Background. The World Health Organization has emphasized the need to protect healthcare workers who risk their lives when facing COVID-19. To guarantee mental health and psychological support to health personnel in the face of the pandemic, the Cuban State implemented an intervention program in Mental Health and Psychosocial Support. Objective: To evaluate the main emotional impacts of COVID-19 on health workers in Havana. Methods: Cross-sectional descriptive study of an intentional sample of 324 health workers from Havana, who responded to an online survey on Google Form, distributed through social networks between the months of October and November 2021. Descriptive statistical techniques were used and data processing was carried out with the SPSS v.25 program. Results: More than half of the health workers surveyed reported fatigue, stress, anxiety, overwhelm, insecurity and annoyance; and more than a third presented high levels of emotional and psychological discomfort. It was evident that the emotional and psychological impacts of the pandemic remain at similar magnitudes to those known in other countries. Conclusions: Scientific evidence is offered on the prevalence of negative emotional impacts of the pandemic on Cuban health personnel, which contributes to the prevention of its consequences on their professional and social performance. Keywords: COVID-19; health workers; mental health, emotional impact, psychological impact.